INVESTIGATION INTO IMMUNIZATION DROPOUT RATE AND ITS DETERMINANTS AMONG CHILDREN AGED 0-23MONTHS IN UHUNMWONDE LGA, EDO STATE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: Immunization is a critical public health intervention that significantly reduces childhood morbidity and mortality associated with vaccine-preventable diseases. Despite its effectiveness, challenges persist in achieving optimal immunization coverage, particularly in low and middle-income countries like Nigeria. High dropout rates among children aged 0-23 months in Uhunmwonde LGA, Edo state, highlight the need for targeted interventions to address barriers to immunization completion.Objective: This study aimed to assess factors influencing immunization dropout rates among children aged 0-23 months in Uhunmwonde LGA, Edo state, Nigeria. Specifically, it aimed to examine socio-demographic factors associated with dropout rates, determine actual dropout rates in specified wards, identify contributing factors, and propose solutions for improving immunization coverage in the region.Method of Analysis: The study utilized a cross-sectional design to collect data on immunization coverage and dropout rates across specified wards in Uhunmwonde LGA, Edo state. Socio-demographic factors associated with dropout rates were analyzed using bivariate associations, while actual dropout rates and contributing factors were determined through statistical analysis of collected data.Results: Analysis revealed varying immunization coverage and dropout rates across antigens and age groups. BCG had the highest coverage at 99.02%, while IPV2 at fourteen weeks had the lowest at 59.17%. Dropout rates ranged from 0.98% for BCG to 99.02% for zero dose, indicating significant gaps in completing immunization schedules. Significant associations were found with socio-demographic factors, such as younger caregivers aged 15-34 displaying lower dropout rates. Health facility-related factors, including health worker attitude and vaccine stockouts, also contributed to dropout rates.Conclusion: High dropout rates among children aged 0-23 months in Uhunmwonde LGA, Edo state, indicate significant challenges in achieving optimal immunization coverage. Addressing barriers such as access to healthcare services, awareness about vaccination importance, socio-economic disparities, and security challenges is crucial for improving immunization coverage and reducing the burden of vaccine-preventable diseases in the region.